ISOLASI DAN IDENTIFIKASI JAMUR-JAMUR PENDEGRADASI AMILOSA PADA EMPELUR TANAMAN SAGU (Metroxylon sagu Rottb.) - Yulina Ade, Filza (Edu Research, 2013)
Some microorganism can be amylose degradation which have large starchcomponent in plant. A research about isolation and identification of fungusdegradation in core of plant sago (Metroxylon sagu Rottb.), had been doneusing purposive sampling method, isolation and selection of microbes alreadyexisted in sago. This research aimed to look fungus species in core of plant sagowhich amylose degradation potential and to know can be able in amylosedegradation. Result showed that species of fungus have amylose degradationpotential. Kinds of fungus isolate which founded are Aspergillus niger,Geotrichum sp., Aspergillus oyzae dan Rhizopus oryzae. All the fungus isolatehave good and big potential in amylose degradation with afforded to starchdegrade at medium to fast rate